Occupational Training in Proprietary Schools and Technical Institutes - Freeman, Richard B. (The Review of Economics and Statistics, 1974)
JOB skills and human capital are acquired by a variety of activities in diverse institutional settings, ranging from parental investment in children to on-the-job training at work places. The purchase of occupational training from for-profit 'proprietary' schools and institutes is a significant, often neglected, mode of obtaining skills.' In 1971, approximately 1.4 million students enrolled in proprietary schools to prepare for work in such areas as truckdriving, electronics, cosmetology, cooking, and floristry, to name just a few. The schools provide an important example of the competitive for-profit education of voucher and performance contract proposals. With recent concern about the allocation of educational resources between academic and vocational schooling,2 possible differences in the social rate of return to for-profit and academic training have obvious policy implications. This paper investigates proprietary school job training in the United States and its impact on the earnings and occupational position of male workers. Section I presents information about proprietary schools and their distinctive operating characteristics; Section II estimates the effect of training on the earnings and occupational status of male workers and uses these estimates to obtain private and social rates of return under various assumptions about direct and indirect (= time) costs of education. I. The Proprietary School Training Market